Optimalisasi Pembelajaran Bahasa Arab Melalui Media Wayang Gambar sebagai Sarana Pengembangan Kosakata Siswa DTA Al-Falah 2 Desa Margasari - Syifa Nur Fauziyah; Yuwan Fijar Anugrah; Nurhaimin (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The learning of the Arabic language plays a strategic role in Islamic education, particularly in mastering Islamic literature and worship. However, this learning process often faces challenges, such as low student interest, monotonous teaching methods, and limited learning media. At DTA Al-Falah 2 in Margasari Village, these issues have resulted in low student vocabulary mastery. To address this, this community service initiative aims to optimize Arabic language learning through an innovative medium called wayang gambar (illustrated puppets). This medium is designed to create an interactive and enjoyable learning experience, thereby increasing students' interest and vocabulary skills. The methods used include problem identification, program planning, teacher training, implementation of learning using wayang gambar, and evaluation through pre-test and post-test assessments. The results of this initiative show that the use of wayang gambar is effective in improving students' vocabulary mastery. This program is expected to serve as a sustainable learning model to enhance the quality of Arabic language education in other Islamic educational institutions, particularly at DTA Al-Falah 2.